2019
DOI: 10.1371/journal.pone.0218258
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification integrating genetic data for factor VIII inhibitor development in patients with severe hemophilia A

Abstract: Replacement therapy in severe hemophilia A leads to factor VIII (FVIII) inhibitors in 30% of patients. Factor VIII gene (F8) mutation type, a family history of inhibitors, ethnicity and intensity of treatment are established risk factors, and were included in two published prediction tools based on regression models. Recently investigated immune regulatory genes could also play a part in immunogenicity. Our objective is to identify bio-clinical and genetic markers for FVIII inhibitor development, taking into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…There is broad recognition that genetic factors play a role in determining which patients develop inhibitors and which do not (3)(4)(5)(6)(7)(8). However, identifying the genetic markers of immunogenicity is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…There is broad recognition that genetic factors play a role in determining which patients develop inhibitors and which do not (3)(4)(5)(6)(7)(8). However, identifying the genetic markers of immunogenicity is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…A different approach would be to incorporate genomic information at baseline, such as HLA class II haplotypes 17 , 18 and/or gene variants of other genes previously associated with inhibitor formation (eg, IL‐10 and CTLA‐4). 19 …”
Section: Discussionmentioning
confidence: 99%
“…For example, much information could be gained by measuring the antibody response over time, 15 as was done in a recent study by Reipert et al 16 Interestingly, this study found that during treatment, the appearance of IgG1 antibodies, followed by IgG3 antibodies, was a strong biomarker of future inhibitor development. A different approach would be to incorporate genomic information at baseline, such as HLA class II haplotypes 17,18 and/or gene variants of other genes previously associated with inhibitor formation (eg, IL‐10 and CTLA‐4) 19 …”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether the patients who developed inhibitors in this cohort were exposed to danger signs such as infections, surgeries or the previous intensity of treatment that could be involved in the generation of immunogenicity against the administered factor VIII. 24,25 It should also be considered that, in real life conditions, patients may not communicate the treatment they were previously receiving to a new clinic responsible for their care if they change institutions; a patient may be treated with a completely different drug, and this is a determining variable.…”
Section: Discussionmentioning
confidence: 99%